Solidarity and Brokenness in the Body of Christ: Receptive Ecumenism and First Corinthians. - Lawson, James (Ecumenical Review, 2024)
This article considers what the language of the body of Christ in Paul's First Letter to the Corinthians implies about the nature of the church as an exercise in embodied solidarity, suggesting that it might helpfully be used to offer scriptural warrant for the relatively recent practice of receptive ecumenism. It suggests that the ecclesiological assumptions implicit in the practice of receptive ecumenism can be articulated as a recovery of a particular Pauline "ecclesiology as Christology." However, if this vision is to be of any use, it must address situations in which its basis in embodied solidarity appears to be under threat. Following a recent commentary on the epistle (and drawing in other reflections), it considers whether the language of pathology is a helpful way of articulating such threats and, if not, what alternative language might be preferable for this task.